Measuring the Impact of a Full Service Grocery Store in a Food Desert. Issue 2 (June 2021) - Schneider, Kellie; Castellanos, Diana Cuy; Fernando, Felix; Holcomb, Jeanne A.
Food deserts, areas in which it is difficult to obtain affordable, nutritious food, are especially problematic in low-income neighbourhoods. One model for addressing food hardship and unemployment issues within low-income food deserts is a cooperative grocery store. Through the cooperative model, the grocery store can serve as a cornerstone to address socio-economic marginalisation of low-income neighbourhoods and improve the health and well-being of its residents. It is important for communities and policymakers to be able to assess the effectiveness of these types of endeavours beyond traditional economic factors such as profitability. This article uses a systems engineering approach to develop a framework for measuring the holistic impact of a cooperative grocery store on community health and well-being. This framework encompasses values that characterise the relationship between food retail, economic viability and social equality. We develop a dashboard to display the key metrics for measuring the economic, social and environmental indicators that reflect a grocery store's social impact. We demonstrate the usefulness of the framework through a case study of a full-service cooperative grocery store that is planned within the city of Dayton, OH.